HUMAN RESOURCE SKILLS DEVELOPMENT STRATEGIES BASED ON LOCAL WISDOM IN THE INDUSTRY 4.0 ERA - Alsilva Damayanti; Fansha Tio Anugrah; Sulastini; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore how local cultural values are integrated into human resource development (HRD) strategies to address workforce transformation in the Industry 4.0 era. This phenomenon is critical as technological advancements demand training models that not only focus on technical competencies but also incorporate local social and cultural contexts. A qualitative approach with a case study design was employed to investigate a community-based training program in a local Indonesian training institution. Data were collected through semi-structured interviews, participant observation, and document analysis involving five key informants selected through purposive and snowball sampling techniques. Thematic analysis revealed three major themes: the internalization of gotong royong (mutual cooperation) in the training curriculum, reinforcement of local work ethic as a foundation for discipline, and collective responsibility as a collaborative learning strategy. The findings indicate that HRD programs based on local values can foster a more participatory, adaptive, and contextually relevant learning ecosystem. Theoretically, this study contributes to the enrichment of Human Capital Theory, Transformational Learning, and Cultural Embeddedness frameworks. Practically, it offers an alternative community-based training model that supports workforce readiness amidst industrial transitions. The study recommends the development of national training policies that are more responsive to local cultural contexts.